2022
DOI: 10.1016/j.jaac.2021.05.022
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Computerized Interpretation Bias Training for Disruptive Mood Dysregulation Disorder: A Fast-Fail Study

Abstract: To examine targeted, mechanism-based interventions is the next generation of treatment innovation. Biased threat labeling of ambiguous face emotions (interpretation bias) is a potential behavioral treatment target for anger, aggression, and irritability. Changing biases in face-emotion labeling may improve irritability-related outcomes. Here, we report the first randomized, double-blind placebo-controlled targeted trial of interpretation bias training (IBT) in youths with chronic, severe irritability. Method: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 56 publications
1
11
0
1
Order By: Relevance
“…Similarly, Wells et al 15 trained children with severe problem behaviours to improve their ability to recognize sad, fearful, angry, and neutral expressions and found that their behavioural problems subsequently decreased. In contrast, some studies have found that emotional recognition training had no evident effects on irritability symptoms 16 as well as state anger, aggression, and hostile attribution assessed in a game context. 17 The mixed results in previous studies suggest that emotional recognition training may affect behaviour indirectly.…”
Section: Introductionmentioning
confidence: 86%
“…Similarly, Wells et al 15 trained children with severe problem behaviours to improve their ability to recognize sad, fearful, angry, and neutral expressions and found that their behavioural problems subsequently decreased. In contrast, some studies have found that emotional recognition training had no evident effects on irritability symptoms 16 as well as state anger, aggression, and hostile attribution assessed in a game context. 17 The mixed results in previous studies suggest that emotional recognition training may affect behaviour indirectly.…”
Section: Introductionmentioning
confidence: 86%
“…116 Programs are also being designed to correct perceptual biases in youth that misinterpret ambiguous facial expressions as angry or threatening. 72 Effective intervention depends on a functional understanding of the behaviors, including factors that trigger, reinforce, or excuse the behavior, either in the present or historically. Once established, maladaptive coping strategies may persist even if they are no longer effective or if the environment has changed, unless patterns of reinforcement are addressed and the child or family system is taught new skills.…”
Section: Treatmentmentioning
confidence: 99%
“…Contrarily, the recent study failed to nd the effectiveness of interpretation bias training, which was a signi cant shift toward labeling ambiguous faces as happy, on irritability improvement 14 . These Findings suggested the need to integrate multiple features (i.e., behavioral de cits, neural correlates, phenotypic speci city) to achieve comprehensive understanding of the underlying neurobiological mechanisms of irritability in youth.…”
Section: Introductionmentioning
confidence: 95%
“…These Findings suggested the need to integrate multiple features (i.e., behavioral de cits, neural correlates, phenotypic speci city) to achieve comprehensive understanding of the underlying neurobiological mechanisms of irritability in youth. Additionally, aberrant threat interpretation may be considered as one cognitive pathway to emotional problems across internalizing and externalizing phenotypes of which irritability can be a critical part 14 . Therefore, in this study, we identify how the behavioral phenotype (irritability severeness) and neural correlates in uence on aberrant threat interpretation in youths with DMBD.…”
Section: Introductionmentioning
confidence: 99%